Dynamic features of three-dimensional helical gears under sliding friction with tooth breakage. (December 2016) - Jiang, Hanjun; Liu, Fuhao
Abstract: Mass eccentric and mesh stiffness variation induced by tooth breakage will change the dynamic features of helical gears. However, the internal excitation in helical gears under sliding friction with tooth breakage is seldom considered to reveal the dynamic features. In this study, the calculation method of mesh stiffness in helical gears with tooth breakage is proposed based on the time-varying contact line. A three-dimensional analytical helical gear pair model is developed by considering the mass eccentric and mesh stiffness induced by tooth breakage with sliding friction. The effects of tooth breakage on the dynamic responses of helical gears are performed. The results show that the amplitude modulation phenomenon emerged in the dynamic transmission error by considering the mass eccentric caused by tooth breakage. The oscillation of the dynamic response change significantly in the tooth breakage area, especially with the growth of the breakage size. Sliding friction plays a certain role in inhibiting the amplitude of the frequency. Tooth breakage results in the presence of rotational frequency and sidebands around mesh frequency and its harmonics. The rotational frequency increases significantly by considering the mass eccentricity due to tooth breakage defect. Highlights: Calculation method of meshing stiffness with tooth breakage in helical gears is proposed. A three-dimensional analytical helical gear pair model is developed under sliding friction with mass eccentric. Effects of tooth breakage on the dynamic characteristics of helical gears under sliding friction are investigated.